2004
DOI: 10.1093/jee/97.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Role of Egg Density on Establishment and Plant-to-Plant Movement by Western Corn Rootworm Larvae (Coleoptera: Chrysomelidae)

Abstract: The effect of egg density on establishment and dispersal of larvae of the western corn rootworm, Diabrotica virgifera virgifera LeConte, was evaluated in a 3-yr field study. Implications of these data for resistance management plans for Bt crops are discussed. Viable egg levels of 100, 200, 400, 800, and 1600 eggs per infested plant were evaluated in 2000, 2001, and 2002. A 3200 viable egg level was also tested in 2001 and 2002. All eggs were infested on one plant per subplot in a field that was planted to soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 0 publications
1
60
0
Order By: Relevance
“…Although we only have one colony per treatment, our data suggest that selection for resistance may be minimal when neonate larvae are exposed to Bt corn but development is completed on isoline corn (the Neonate-exposure colony was not significantly different from the Control colony for any parameter of resistance). However, in a scenario where initial development occurs on grassy weeds and the weeds are then sprayed with herbicide, or in a seed-mix scenario where isoline food resources are significantly depleted forcing larvae to move (24), resistance might be expected to evolve, given that survival of the Lateexposure colony on Bt corn relative to isoline survival was significantly (3.8-fold) greater than the Control colony in the field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we only have one colony per treatment, our data suggest that selection for resistance may be minimal when neonate larvae are exposed to Bt corn but development is completed on isoline corn (the Neonate-exposure colony was not significantly different from the Control colony for any parameter of resistance). However, in a scenario where initial development occurs on grassy weeds and the weeds are then sprayed with herbicide, or in a seed-mix scenario where isoline food resources are significantly depleted forcing larvae to move (24), resistance might be expected to evolve, given that survival of the Lateexposure colony on Bt corn relative to isoline survival was significantly (3.8-fold) greater than the Control colony in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Temperatures in such a greenhouse in late June in Missouri are often 50 -65°C. Under these conditions, larvae leave the hot and drying soil in search of a more suitable environment (12,24). Larvae were captured in water pans below each root ball, and were transferred to 95% ethanol at least twice daily.…”
Section: Methodsmentioning
confidence: 99%
“…Western corn rootworm survival was evaluated by suspending the plant roots and surrounding soil in mesh bags (New cabbage, USA) over water filled pans (6.65 L) in a greenhouse at day 68, causing the fall of soil‐dwelling invertebrates (Hibbard, Higdon, Duran, Schweikert, & Ellersieck, 2004). WCR larvae were counted twice a day for 12 days.…”
Section: Methodsmentioning
confidence: 99%
“…However, to permit reasonable comparison with seed mixture studies in the future, we include the probability of leaving a nontransgenic plant, Z, the probability of leaving a transgenic plant, V, and the proportion surviving dispersal as neonates, SM, in the model. The data of Hibbard et al (2004) observed 66% of neonates on the initially infested roots. Therefore, we set Z ϭ 0.5 and SM ϭ 0.5 (Onstad 2006).…”
Section: Submodel For Larvaementioning
confidence: 95%